2004
DOI: 10.1203/00006450-200409000-00070
|View full text |Cite
|
Sign up to set email alerts
|

47 High-Flow Nasal Cannula Cpap Versus Infant Flow Nasal Cpap in Newly-Extubated Neonates <1250G

Abstract: Background: Intra-uterine growth restriction (IUGR) is an important risk factor for perinatal morbidity and mortality in prematurity. Placental insufficiency leading to chronic fetal hypoxemia is a well known cause for IUGR. Therefore, the aim of the study was to establish a mouse model for the experimental induction of IUGR caused by reduced maternal inspiratory oxygen to obtain a chronic fetal hypoxemia. Besides auxological data for evaluation of growth restriction, pulmonary surfactant protein (SP) mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It does, however, suggest that there is a need for common and consistent terminology when describing whether HFNC is heated or humidified. Of the other six papers that we excluded for not being heated, 27,32,63-66 three 27,32,63 explicitly stated that they were unheated, meaning that three other papers [64][65][66] (of two studies, one 64 reported only as an abstract) may actually have been studies of HHHFNC.…”
Section: Discussionmentioning
confidence: 99%
“…It does, however, suggest that there is a need for common and consistent terminology when describing whether HFNC is heated or humidified. Of the other six papers that we excluded for not being heated, 27,32,63-66 three 27,32,63 explicitly stated that they were unheated, meaning that three other papers [64][65][66] (of two studies, one 64 reported only as an abstract) may actually have been studies of HHHFNC.…”
Section: Discussionmentioning
confidence: 99%